Substantive use of artificial intelligence - Klesel, Michael,Messer, Uwe (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2024)
Artificial intelligence (AI) is becoming increasingly powerful, enabling users to perform tasks more efficiently and effectively. However, not all users are equally able to take advantage of its capabilities. We draw on previous literature that has introduced the concept of “substantive use” - the reflective consideration of how to use a system's features - to better understand individual differences in the context of AI. We contribute to the current literature in three ways: First, we summarize the literature on technology use and describe its relevance for AI-related research. Second, we review the literature and show that IS has already begun to investigate individual differences to understand the use of AI systems. Third, we propose a theoretical model t hat accounts for the direct and configurational effects of individual differences on substantive use behavior. Künstliche Intelligenz (KI) wird immer leistungsfähiger und ermöglicht es den Nutzern, Aufgaben effizienter und effektiver auszuführen. Allerdings sind nicht alle Benutzer gleichermaßen in der Lage, diese Fähigkeiten zu nutzen. Wir stützen uns auf frühere Literatur, die das Konzept
urn:nbn:de:bsz:946-opus4-69359
Keywords: Graue Literatur; Künstliche Intelligenz; Computerunterstützung; Internetnutzung; Theorie